Three‐level neutral‐point‐clamped quasi‐Z‐source inverter with reduced Z‐source capacitor voltage. Issue 3 (1st February 2017) - Yu, Deqing; Cheng, Qiming; Gao, Jie; Tan, Fengren; Zhang, Yu
Abstract : A new three‐level neutral‐point‐clamped quasi‐Z‐source inverter topology is proposed. The topology can effectively reduce the Z‐source network capacitor voltage stress and inhibit the start inrush current, thus low‐voltage capacitors can be selected to reduce the volume and cost of the inverter. In addition, the changed structure will not affect the boost ability and all existing modulation methods can be used directly. The proposed topology is validated by simulations.